Investigation of Teachers' Attitudes Towards Sports in Turkey - Mehmet Şakir Salar; Hulusi ALP (Universitas Majalengka, 2021)
This research was conducted to examine the Attitudes of Teachers working in public schools towards Sports in terms of Different Variables. The data of the research were obtained from 403 teachers working in Aydın during the 2020-2021 academic year. As the data collection tool,